Industry 4.0 Perception Among Employees: A Study in the Textile Industry - KAYA, Özlem; AYTAÇ, Sevinç Serpil (PEARSON JOURNAL, 2023)
The aim of this study is to determine the expectations of individuals in different age groups working in the textile industry regarding the changes that may occur with Industry 4.0, their predictions and the values they attribute to work, thus creating an idea about the future of working life. In this study, participants were asked demographic questions such as age, gender, education and employment status, profession, length of service, current position and time spent in working life; Additionally, the Industry 4.0 Scale developed by Rıza Demir (2019) and the Meaning of Work Scale developed by Steger et al. (2011) and whose Turkish validity and reliability were confirmed by Akın et al. (2013) were used. With the Industry 4.0 Scale, employees' knowledge levels about Industry 4.0, their thoughts about robotic developments, their thoughts and attitudes about the possible effects of Industry 4.0 on working life and possible changes in recruitment were evaluated. The Meaning of Work Scale measures individuals' attitudes towards the work they do and the meaning of their work. The scales are in 5-point Likert type. Convenience sampling method was used in the study. The online survey form prepared via Google form was applied by the Human Resources directorate of the textile factory where the application was carried out, by sending it online to the e-mail addresses of people involved in working life. According to the data obtained from 292 people, it has been observed that the expectations of employees in different age groups from business life vary according to age groups, while the meaning of work and awareness of Industry 4.0 do not change according to age groups. A positive and significant relationship was determined between the expectations of employees in different age groups from business life and the meaning of work. In this context, some suggestions have been developed about the textile industry and its future in parallel with the changes that may occur with Industry 4.0.